Early Egyptian miscellanies discussions and essays on Predynastic and Early Dynastic Egypt - Sperveslage, Gunnar (Golden House Publications, 2022)
"This book collects papers from various authors on Predynastic and Early Dynastic Egypt, covering archaeology, iconography, philology, lexicography, history, and history of research. The contributions provide insight into current research and offer new theories and observations on specific objects and aspects. This includes for instance neglected details of well-known objects, detailed discussion of forgotten objects, new interpretations of inscriptions, and analysis of hieroglyphic signs and their functions."
Keywords: Geschichte; Ägypten -- Altertum; Egypt / History / Early Dynastic Period, ca. 3100-ca. 2686 B.C.; Egypt / Antiquities; Antiquities; Egypt; History; Aufsatzsammlung